2015
DOI: 10.1080/10400435.2015.1011758
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Braille Learning Application for Visually Impaired Students in Bangladesh

Abstract: Visually impaired students (VIS) are unable to get visual information, which has made their learning process complicated. This paper discusses the overall situation of VIS in Bangladesh and identifies major challenges that they are facing in getting education. The Braille system is followed to educate blind students in Bangladesh. However, lack of Braille based educational resources and technological solutions have made the learning process lengthy and complicated for VIS. As a developing country, Bangladesh c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…Therefore, prototypes of games adapted for the visually impaired can, at least in part, help to meet the need for new teaching resources in a universe demanding of these, especially in education for the visually impaired, since it provides the development of skills using other senses besides of vision. In line with our work, a previous study demonstrated that the development of a specific design on mobile devices focused on braille application (mobile phone-based Braille application, "mBRAILLE"), allowed individuals with vision loss to learn English and, in the pilot study, users approved this technology (Nahar, et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, prototypes of games adapted for the visually impaired can, at least in part, help to meet the need for new teaching resources in a universe demanding of these, especially in education for the visually impaired, since it provides the development of skills using other senses besides of vision. In line with our work, a previous study demonstrated that the development of a specific design on mobile devices focused on braille application (mobile phone-based Braille application, "mBRAILLE"), allowed individuals with vision loss to learn English and, in the pilot study, users approved this technology (Nahar, et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Nahar et al (2015) developed a mobile phone-based Braille learning application called “mBraille,” compatible with the Android application. The application was found useful to visually impaired students with an overall satisfaction level of 4.53 out of 5 in the survey.…”
Section: Resultsmentioning
confidence: 99%
“…On completion of the task, vibrio-tactile feedback is provided by [20] and [21]. An educational application named mBraille was designed for learning English and Bengali [38]. Braille-to-text conversion is also performed in other languages such as Hindi, Tamil, Urdu, Odia, Arabic, Chinese, Bengali, Telugu, Malayalam, and Kannada [18,[39][40][41][42][43][44][45].…”
Section: Braille Input Mechanismmentioning
confidence: 99%